Physiological and nutrition-related challenges as perceived by spinal cord-injured endurance hand cyclists - Gordon, R. E.; Scrooby, B.; Havemann-Nel, L. (Applied Physiology, Nutrition, and Metabolism, 2024)
This study explored the perceptions of spinal cord-injured (SCI) endurance hand cyclists regarding their physiological and nutrition-related challenges and the perceived impact of these challenges on nutritional intake and exercise capacity. This was an interpretive qualitative descriptive study in which semi-structured interviews were conducted with 12 adult South African national-level SCI endurance hand cyclists. Thematic analysis was used to explore perceptions regarding physiological and nutrition-related challenges and the impact thereof on nutritional practices and exercise capacity. Four themes emerged from the interviews: (i) physiological challenges experienced, (ii) nutrition-related challenges experienced, (iii) changes in nutritional practices, and (iv) compromised exercise capacity. The SCI endurance hand cyclists reported a number of physiological and nutrition-related challenges. Bowel and bladder challenges, limited hand function, muscle spasms, thermoregulatory challenges, pressure sores, menstrual periods, and low iron levels/anaemia were perceived to predominantly impact food and fluid intake (restrict intake) and compromise exercise capacity. This information can assist to devise tailored guidelines aimed to optimise fluid intake, overcome bladder challenges and ensure adequate nutritional intake in light of limited hand function.